High interpatient variability in response to mycophenolic acid maintenance therapy in patients with ANCA-associated vasculitis - Schaier, Matthias; Scholl, Markus; Scharpf, Dominik; Schmitt, Wilhelm; Schwenger, Vedat; Zeier, Martin; Sommerer, Claudia (Nephrology, dialysis, transplantation, 2015)
Background: Mycophenolic acid (MPA) is used in the maintenance therapy of antineutrophil cytoplasm antibody-associated systemic vasculitis (AASV). MPA exerts its immunosuppression by inhibiting inosine 5′-monophosphate dehydrogenase (IMPDH), depleting activated lymphocytes of guanine nucleotides and retarding their proliferation. The purpose of our study was to examine the correlation between clinical outcome and pharmacokinetic-pharmacodynamic (PD) relationships of MPA in patients with AASV.Methods: We studied 358 Caucasian control patients without any MPA therapy to examine basal IMPDH activity. Thirty Caucasian patients with AASV under maintenance therapy with mycophenolate mofetil (MMF) underwent therapeutic drug monitoring. Results: We observed a high interindividual variability with regard to basal IMPDH activity in patients without any MPA treatment (0.8-35 nmol/mg protein/h). Patients were followed for a mean (±SD) period of 22 ± 8 months. During the observation period, seven patients had a relapse with an elevated Birmingham Vasculitis Activity Score of 9.2 ± 6. The basal IMPDH activity (Abasal) in patients who subsequently relapsed was raised at baseline, before receiving their first dose of MMF, and further increased at the time of relapse, when compared with stable patients. Patients with a relapse during the maintenance therapy had significantly higher levels of IMPDH activity [IMPDH enzyme activity curve (AEC) (0-12)] than stable patients (P = 0.001), indicating inadequate IMPDH suppression. MPA-AUC (0-12) was significantly decreased in relapse patients, in contrast to stable patients (P < 0.05). Conclusions: Due to the highly variable response to maintenance therapy with MPA, PD drug monitoring is a new tool for detecting inadequate immunosuppression in AASV patients.